PERBANDINGAN KADAR GLUKOSA DARAH SEWAKTU METODE GOD-PAP DAN METODE POCT PADA PASIEN DIABETES MELITUS DI RUMAH SAKIT TINGKAT III 04.06.01 WIJAYA KUSUMA PURWOKERTO - Rifki Firdaus Iksan (Journal of Nursing and Health, 2025)
Diabetes is the main cause of blindness, kidney failure, heart disease, stroke, and can result in amputation of body parts. Controlling blood sugar levels is very necessary for diabetes mellitus sufferers, apart from using medical therapy, maintaining a diet and doing exercise are also very helpful in controlling blood sugar levels. According to data from the Banyumas Regency Health Service (2022), the number of people suffering from the non-communicable disease diabetes mellitus is 23,461 spread across 27 sub-districts in Banyumas Regency and increases every year. The research was carried out experimentally by comparing the results of checking blood glucose levels using the GOD-PAP and POCT methods. The parameters of this research are the independent and dependent variables, the independent variable is the GOD-PAP method with the POCT method, the dependent variable is glucose levels in patients. The statistical test in this study used the Kolmogorov-Smirnov test to determine the significance of the blood glucose results of the GOD-PAP method and POCT method. With significance (p<0.05), which shows that H0 or H1 is accepted or rejected. The samples in this study were 62 samples with the results of the examination showing glucose levels using the GOD-PAP method, a minimum glucose value of 70 mg/dL, a maximum of 289 mg/dL and an average of 119 mg/dL. POCT method glucose levels, the minimum glucose value is 85 mg/dL, the maximum is 363 mg/dL and the average is 129 mg/dL. The P-value from the calculation results is 0.000, so it can be concluded that H1 is accepted, namely that there is a difference in the glucose level results of the GOD-PAP method and the POCT method at TK III Hospital 04.06.01 Wijaya Kusuma Purwokerto.